(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on how students will enhance their allowances by using budget allocation strategies. One of the most common problems of Grade 12 general academic strand students is that they are unaware of their daily expenditures. They lack knowledge about how to properly organize their budget and manage their spending. Based on the result of the study, using budget allocation strategies for educational expenses positively affected the budget management of Grade 12 GAS students in terms of (1) food allowances (38% of their allowances were allocated to food), (2) school supplies (34% of their allowances go to school materials and buying unnecessary things), and (3) external projects (28% go to program tickets that are not school-related and mismanagement of allowance). Based on the summary of the findings, the following recommendations were made by the researchers on how Grade 12 GAS students should allocate their allowances.